(untitled) (Revista de Ciências Agroveterinárias, 2007)
This work was carried out in order to study the prevalence of Eimeria and Isospora species in swine from Videira county, State of Santa Catarina, Brazil. Faeces samples were collected monthly from the rectum of animals, from August 2001 to July 2003. A total of 1150 samples, 290 not nursing sows, 300 pregnant sows, 300 sows in lactation and 260 piglets from seven to 20 days from both male and female, was assessed. The samples were packed in plastic bags properly identified, placed into a styrofoam box and sent to the Parasitology and Parasitary Diseases Laboratory of the Santa Catarina State University (UDESC) in Lages, SC, Brazil. The samples were submitted to the centrifugation-fluctuation in sugar modified technique and analyzed using optical microscopy. The positive samples were placed individually in a glass recipient with 2.5% potassium bichromate solution and kept in an acclimatized chamber with a controlled temperature of 27 ± 1ºC, relative humidity above 70% and in scotophase for the oocysts sporulation. The oocysts were concentrated by the centrifugation-fluctuation technique and identified using optical microscopy. From the 1150 samples analyzed, 40 presented oocysts of coccidia, with a prevalence of 3.48%. Seven species of Eimeria were identified: E. neodebliecki, E. debliecki, E. suis, E. porci, E. scabra, E. perminuta, E. spinosa, and one species of Isospora: I. suis. The highest prevalence of E. debliecki was in lactation sows (4.33%) and in piglets (5.77%). I. suis was prevalent in piglets (5%). From the 691 oocysts identified, 60.49% (418/691) were of the Eimeria genus and 39.51% (273/671) were from Isospora. The species Eimeria noedebliecki and I. suis contributed the most to the oocyst production, totalizing 39.36% e 39.51% to the final percentage.